Household Devices to Provide Hygiene of Life: Efficiency, Power-Saving and Ecologic Design - S. L. Kalachev; I. A. Makhotina; M. A. Polozhishnikova (Вестник Российского экономического университета имени Г. В. Плеханова, 2022)
Washing machines and dish washers, vacuum cleaners are goods that in line with their functional efficiency are characterized by high power-intensity, which increases in proportion to their growing number in households. The authors give statistic data dealing with provision of the population of the EC and the Russian Federation with these goods, their sales, total annual consumption of water and electric power in the EC. The ranges of operation indicators, possible service life of devices are stated, as well as the information of the Eurasian Economic Committee about their work in the EC (average work per year, service life, etc.). Measures taken by the Euro-committee in order to cut power and water consumption necessary for these household devices are characterized and the results expected by the Euro-committee from these measures are shown. Indicators of power-efficiency attained by EC manufacturers are mentioned. It is pointed out that in order to ensure power-saving and prevent the arrival of outdated goods on the EAEU territory the Eurasian Economic Committee are working out measures similar to those approved in the EC. The technical regulations (TREAEC) fixing the requirements of power efficiency was adopted. Comparative analysis of norms and requirements to power-efficiency and eco-design in EC and EAEU showed the necessity to revise TREAEU.